(untitled) (Journal of the College of Education for Women, 2022)
Due to the difficulties that Iraqi students face when writing in the English language, this preliminary study aimed to improve students’ writing skills by using online platforms remotely. Sixty first-year students from Al-Furat Al–Awsat Technical University participated in this study. Through these platforms, the researchers relied on stimuli, such as images, icons, and short titles to allow for deeper and more accurate participations. Data were collected through corrections, observations, and feedback from the researchers and peers. In addition, two pre and post-tests were conducted. The quantitative data were analysed by SPSS statistical Editor, whereas the qualitative data were analyzed using the Piot table, an Excel sheet. The results have shown improvement of more than (0.5). This indicates that the study is effective and beneficial for the Iraqi students. Moreover, students were generally satisfied with the experience, as it allowed them to easily communicate, research and rely on themselves when learning to write in English as a foreign language. In addition, semiotic awareness and learning via e-learning platforms can be greatly adopted in teaching English in Iraq. The study has further concluded that there is an improvement in the performance of the Iraqi learners, and that their writing skills were enhanced after the improvement of their semiotic awareness. The is, the improvement of their semiotic awareness has deepened their understanding and enhanced their ability to analyze and criticize. It also developed their communication skills and motivate them to write better and search for details